2006
DOI: 10.1038/sj.onc.1210076
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced expression of the cellular adhesion molecule L1CAM confers anti-apoptotic protection and chemoresistance in pancreatic ductal adenocarcinoma cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by rapid tumor progression, high metastatic potential and profound chemoresistance. We recently reported that induction of a chemoresistant phenotype in the PDAC cell line PT45-P1 by long-term chemotherapy involves an increased interleukin 1 beta (IL1b)-dependent secretion of nitric oxide (NO) accounting for efficient caspase inhibition. In the present study, we elucidated the involvement of L1CAM, an adhesion molecule previously found in other malignanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 26 publications
7
102
0
Order By: Relevance
“…A prior publication suggested that CD171 is not expressed in PDAC in situ 55 ; however, a subsequent report demonstrated CD171 expression in 80% of G2 and 100% of G3 PDAC tumors, 56 in agreement with our current findings. That highly aggressive PDAC cells would express CD171 is not unexpected, because CD171 mediates migratory and invasive processes in neural and melanoma cells and epithelial tumors of the breast, ovary, and colon.…”
Section: Discussionsupporting
confidence: 93%
“…A prior publication suggested that CD171 is not expressed in PDAC in situ 55 ; however, a subsequent report demonstrated CD171 expression in 80% of G2 and 100% of G3 PDAC tumors, 56 in agreement with our current findings. That highly aggressive PDAC cells would express CD171 is not unexpected, because CD171 mediates migratory and invasive processes in neural and melanoma cells and epithelial tumors of the breast, ovary, and colon.…”
Section: Discussionsupporting
confidence: 93%
“…L1CAM upregulates Olig2 to suppress expression of p21 WAF1/CIP1 . In addition, a number of studies showed that L1CAM is associated with chemoresistance of ovarian and pancreatic cancers (Stoeck et al, 2007;Sebens Müerköster et al, 2007;Gavert et al, 2008;Raveh et al, 2009). We have recently found that differential expression of L1CAM in GSCs contributes to therapeutic resistance.…”
Section: Specific Cell Surface Molecules In Glioblastoma Stem Cellsmentioning
confidence: 96%
“…A study with 15 tissues of undifferentiated (anaplastic) pancreatic cancer and pancreatic carcinoma with osteoclast-like giant cells revealed L1CAM positivity in 80 % of the analysed samples (Bergmann et al, 2010a). Our group was the first who documented considerable L1CAM expression in a small series of PDAC samples (Sebens Müerköster et al, 2007). An extended analysis with 110 primary PDAC tissues, 15 lymph node and 14 liver metastases revealed tumoral L1CAM expression in 92,7 %, 80 % and 100 % of the samples, respectively (Bergmann et al, 2010b).…”
Section: L1cam Expression In Pancreatic Tumorsmentioning
confidence: 59%
“…Stoeck et al also demonstrated that L1CAM in its membrane-bound as well as in its soluble form confers apoptosis resistance in ovarian carcinoma cells towards C2-ceramide, staurosporine, cisplatin and hypoxia. Long-term treatment with the cytostatic drug cisplatin increased L1CAM expression level in ovarian carcinoma cells m130 (Stoeck et al, 2008) which was similarly observed in PDAC cells after long-term incubation with etoposide indicating a role for L1CAM in the acquired chemoresistance of tumor cells (Sebens Müerköster et al, 2007). Immunohistochemical analyses of pancreatic tissues together with data from coculture experiments indicate that L1CAM is not only upregulated during chemotherapy but also under the influence of the cellular microenvironment.…”
Section: L1cam and Apoptosis Resistancementioning
confidence: 90%
See 1 more Smart Citation